Abiotic Typology of the Rivers and Lakes of the Ukrainian Section of the Western Bug River Basin and its Comparison with Results of Polish Investigations - Khilchevskyi, Valentyn K.; Grebin, Vasyl V.; Zabokrytska, Myroslava R. (Ukrainian Hydrometeorological Institute, 2019)
The completed investigation, which are based on the requirements of the EU WFD and rivers typology systems adapted in Ukraine and Poland, allowed us to identify: for the Western Bug river basin within Ukraine 9 abiotic river types, within Poland – 7. In the Western Bug basin is dominated by small and medium rivers of lowlands and uplands of the Eastern Plains on silicate rocks. The Western Bug belongs to very large rivers, the Poltva, the Rata and the Luga belong to large rivers. Within the Ukrainian part of the Western Bug river basin, there are only 2044 rivers, of which 2010 (98.35%) are small rivers. The length of the majority of them (1966 rivers are small) doesn’t exceed 10 km. Middle rivers are 1.45%. Large and very large rivers are 0.15% and 0.05% of their total, respectively.Generally, in the Ukrainian part of the Western Bug basin 8 abiotic types of lakes were identified.
Keywords: Western Bug; rivers; lakes; EU Water Framework Directive; Ukraine; Polish investigations